1998
DOI: 10.1108/02686909810236334
|View full text |Cite
|
Sign up to set email alerts
|

Is the control environment related to financial reporting decisions?

Abstract: The accounting profession’s strong focus on internal control and fraudulent financial reporting has led to new standards relating to internal control and fraudulent financial reporting. The control environment and specifically, management integrity, is an important component. The purpose of this article is to determine if the control environment forces ‐ the tone at the top, codes of conduct, and short‐term targets ‐ are related to financial reporting decisions. The results are based on a survey mailed to 400 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
3

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(9 citation statements)
references
References 3 publications
0
6
0
3
Order By: Relevance
“…Dechow et al [30] investigated the SEC Enforcement Actions for violations of General Accounting Standards, and found that if the CEO was the founder of the company or on the board, earnings manipulation was more common. D'Aquila [31] confirmed that high-level voices had a big impact on the authenticity of a company's financial reports, and were a manifestation of managerial power. Hunton et al [32] conducted a two-stage regression study of the impact of high-level voices on a company's earnings quality, confirming that high-level voices were directly proportional to a company's earnings quality.…”
Section: The Literature On Managerial Powermentioning
confidence: 87%
“…Dechow et al [30] investigated the SEC Enforcement Actions for violations of General Accounting Standards, and found that if the CEO was the founder of the company or on the board, earnings manipulation was more common. D'Aquila [31] confirmed that high-level voices had a big impact on the authenticity of a company's financial reports, and were a manifestation of managerial power. Hunton et al [32] conducted a two-stage regression study of the impact of high-level voices on a company's earnings quality, confirming that high-level voices were directly proportional to a company's earnings quality.…”
Section: The Literature On Managerial Powermentioning
confidence: 87%
“…Scandals such as these are attributable to a weak internal control system (Skinner & Spira, 2003). It is argued that having a strong internal control system is one of the best ways to deter fraud (D'Aquila, 1998;Hemraj, 2004;Holtfreter, 2005;Bierstaker et al, 2006;IIA, 2009). Boards of directors have responsibility over internal control and must timeously communicate to stakeholders such as investors any breakdowns in internal control that could impact investors' decisions (HassabElnaby, Said & Wolfe, 2007;IoD, 2009;Barac & Plant, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Some of the components of control environment for this study are; corporate culture, Competence levels, Quality of audit committees and Integrity and ethics (D'Aquila, 1998& Ramos, 2004. According to Rae & Subramaniam (2006), the core of any organization is its people and they are the engine that drives the organisation.…”
Section: Control Environmentmentioning
confidence: 99%